Memperkecil Dampak Negatif Sosial Media Terhadap Identitas Diri Remaja - Manurung, Haris Benaya; Paulus, Yanto (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2025)
Adolescence is the transition from childhood to adulthood, which usually occurs between the ages of 10 and 21. In this phase, teenagers are very easily influenced by social media, which has now become an inseparable part of their lives. This research uses a qualitative method with a literature study approach and analysis of existing literature. Various parties, including parents, schools, and churches, play an important role in reducing the adverse effects of social media on teenagers. Cooperation between all parties is needed to take preventive measures so that teenagers are not influenced by negative content on social media and can maintain their identity in accordance with Christian values.